Analisis Yuridis Putusan Hakim Dalam Perkara Tindak Pidana Phising Yang Dilakukan Melalui Media Sosial: (Studi Putusan Nomor : 155/Pid.Sus/2018/PN.Cbn) - Indah Eka Putri; Ismansyah (Fakultas Hukum Universitas Andalas, 2023)
Nowadays, social media users are faced with the rise of cyber-phishing, which is carried out using various modes of deception that are troubling. This cybercrime mode causes material and immaterial losses. This crime has been regulated in the Electronic Information and Transaction Law Number 11 of 2008, Article 35 jo. Article 51 paragraph (1) carries a maximum threat of 12 years in prison. One of the cases that has been decided and permanent legal force is Decision Number: 155/Pid.Sus/2018/PN-Cbn. This research will answer the problem of how to analyse the judge's considerations in adjudicating cases of phishing on social media in Decision Number 155/Pid.Sus/2018/PN-Cbn and how to apply criminal sanctions based on the a quo decision. This study uses case approach and statutory approach with juridical-normative research method. Based on the research, juridically, the judge in making a decision only focuses on the demands of the prosecutor and does not consider concurrent criminal acts committed by the defendant, for which the judge can provide a weighting punishment based on Article 65 paragraph (2) of the Criminal Code. Because the statement of the accused is also an important juridical aspect to be considered by the judge in imposing a verdict. This is what makes the punishment given low—only eight months in prison. Then, the application of relatively mild criminal sanctions has not been able to fulfil the goals of punishment and a sense of justice, so it will have an impact on the ineffectiveness of punishment.